Analytical Application of 3-Hydroxy-3-m-tolyl-1-mchlorophenyltriazene in the Spectrophotometric Determination of Molybdenum(VI) - KHAN, SABA; KHANAM, REHANA (Asian Journal of Chemistry, 2010)
A new reagent 3-hydroxy-3-m-tolyl-1-m-chlorophenyltriazene has been used for the spectrophotometric determination of Mo(VI) at 408 nm, in the pH range 2.0-3.0. Beer's law is obeyed in the range (1 to 6) × 105 M. The molar absorptivity and Sandell's sensitivity values are 7184.7 dm3 mol-1 cm-1 and 13.35 ng cm-2, respectively. The method is useful even in presence of several cations and anions.